Evaluation of peri-plaque pericoronary adipose tissue attenuation in coronary atherosclerosis using a dual-layer spectral detector CT - Jia, Yulin; Zou, Lei; Xue, Ming; Zhang, Xiaoyu; Xiao, Xigang (Frontiers in Medicine, 2024)
Purpose: This study aimed to evaluate differences between pericoronary adipose tissue (PCAT) attenuation at different measured locations in evaluating coronary atherosclerosis using spectral CT, and to explore valuable imaging indicators. Methods: 330 patients with suspicious coronary atherosclerosis were enrolled and underwent coronary CT angiography with dual-layer spectral detector CT (SDCT). Proximal and peri-plaque fat attenuation index (FAI) of the most stenotic lumen were measured both on conventional images (CI) and virtual mono-energetic images (VMI) from 40 keV to 100 keV. The slopes of spectral attenuation curve (λ) of proximal and peri-plaque PCAT at three different monoenergetic intervals were calculated. Additionally, peri-plaque FAI on CI and virtual non-contrast images, and effective atomic number were measured manually. Results: 231 coronary arteries with plaques and lumen stenosis were finally enrolled. Peri-plaque FAICI and FAIVMI were significantly higher in severe stenotic vessels than in mild and moderate stenotic vessels (P<0.05), while peri-plaque λ, proximal FAI and proximal λ were not statistically different. Proximal FAI, peri-plaque FAI and periplaque λ were significantly higher in low-density non-calcified plaque (LD-NCP) and non-calcified plaque (NCP) than in calcified plaque (P<0.01). Peri-plaque FAI was the highest in LD-NCP group, while proximal FAI was the highest in NCP group. In severe stenotic vessels and in LD-NCP, peri-plaque FAI was significantly higher than proximal FAI (P<0.05). The manually measured parameters related to peri-plaque PCAT attenuation had positive correlation with the results of peri-plaque FAI measured automatically. Conclusion: Peri-plaque PCAT has much value in assessing coronary atherosclerosis than proximal PCAT. Peri-plaque PCAT attenuation is expected to be used as a standard biomarker for evaluating plaque vulnerability and hemodynamic characteristics.